EFL students’ perception on the use of self-reflection cards for learning English tenses - Rosyida Ekawati; Iqbal Nurul Azhar (Universitas Lampung, 2021)
This study aimed at implementing self-reflection cards (SRCs) in learning English tenses and also explaining students’ perceptions of the use of SRCs in understanding English tenses.A qualitative design was carried out to conduct the study. It focused on interpreting and understanding students’ perception on learning English tenses. The context of study was two classes who were taking English grammar and structure, in particular for the subject matter of English tenses. English tenses were explained orally in the class before students used SRCs to improve their understanding of using English tenses. Data were collected by distributing the questionnaire to the students who participated in two classes with total number of 57 students.The data were classified based on the repetitive and common forms found to assign criteria to the most important aspects related to the objectives of the study. Results indicated that the majority of students participating in the SRCs gamesagreed to all statements in the distributed questionnaire. However, only small number of students responded to their disagreement or neutrality. The majority of positive responses from students are considered as the indicator that the use of SRCs in learning English tenses was successfully implemented in class.